Ulisse all’Isola di Circe (Brussels 1650): Operatic Transformation of Classical Tradition and Dissolution of Stoic Problems - Urbański, Piotr (Werkwinkel, 2015)
The present article is a close reading of the libretto of the first opera (drama musicale) staged in the Netherlands, in Brussels in 1650. The main point of interest is Ascanio Amalteo’s transformation or even breakaway from the classical tradition (esp. Homer and Ovid) to create a work with its own message, quite distant from classical texts but, paradoxically, approaching moral and psychological categories in Neo-Stoic mode. Perhaps it is not by chance that a parallel piece, Calderon’s second play on Circe (after the fiesta entitled El mayor encanto, amor, 1635), i.e. the auto sacramentale entitled Los encantos de la culpa (ca. 1650), is also a significant transformation of the motive done in the spirit of the Counter-Reformation. Both plays are the last allegorical interpretations of Circe myth and for the next two-hundred years the last important literary works about Ulysses.